A Study on the Optimization of High School Buildings for Evacuation Safety: Classroom Layout and Ramps in Korea - Ha-Sung Kong, Chang-Jun Choi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study used the Pathfinder program to evaluate evacuation safety by assuming evacuation training in high school buildings and changing classroom layout. Analysis of the final evacuation requirements for Scenario 2, which currently has a concentration of classrooms on the third floor of the building, showed that Scenario 2 reduced 29.6 seconds to 173.9 seconds compared to Scenario 1's 203.5 seconds. However, the analysis of Scenario 3, in which 10 classrooms and personnel of three grades were placed equally on the left and right sides of the building, showed that the final evacuation requirements were reduced 3.9 seconds to 170.0 seconds compared to Scenario 2, but there was no significant difference. Scenario 3, which has more the efficiency of school year operation by placing classroom layout on the same floor by grade level than Scenario 2, in which more classrooms and students were placed downstairs. In each scenario, an analysis of the final evacuation requirements showed that the evacuation exit T1 on the left side of the building was 28 seconds or more shorter than T3 on the right side of the building. Therefore, it was analyzed that proper classroom layout and ramp facilities in high school buildings ensure evacuation safety